2018
DOI: 10.1007/s00367-018-0556-4
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes due to marine aggregate extraction for beach nourishment in the German Bight (SE North Sea)

Abstract: Facing the predicted rise in global sea level, sandy shorelines are under increasing pressure. In order to counteract the loss of material at eroding coastlines, beach nourishment is considered to be an environmentally friendly approach worldwide. This has resulted in a rising demand for aggregates, which are frequently extracted from the seafloor near the coast. In order to explore the long-and short-term morphological changes of such mining on the seabed, the largest extraction area in the German Bight (West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
(27 reference statements)
1
14
0
Order By: Relevance
“…The comparison of the 2019's bathymetry of the oldest pits with earlier measurements in 2016 and 2017 (Mielck et al, 2018) revealed no significant change indicating that the annual sedimentation rate was below the resolution of our multibeam device (~10 cm). This is in accordance with the very low sedimentation rate (2-18 mm per year) recorded from a muddy depression near the Island of Helgoland, ~80 km south of the study area (Dominik et al, 1978;von Haugwitz et al, 1988).…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…The comparison of the 2019's bathymetry of the oldest pits with earlier measurements in 2016 and 2017 (Mielck et al, 2018) revealed no significant change indicating that the annual sedimentation rate was below the resolution of our multibeam device (~10 cm). This is in accordance with the very low sedimentation rate (2-18 mm per year) recorded from a muddy depression near the Island of Helgoland, ~80 km south of the study area (Dominik et al, 1978;von Haugwitz et al, 1988).…”
Section: Discussionmentioning
confidence: 51%
“…The dredging pits themselves reveal a muddy surface, even 35 years after sediment excavation. This is due to low sedimentation rates in the southern North Sea and the study area (Dominik et al, 1978;von Haugwitz et al, 1988;Mielck et al, 2018) brought about by the combination of a lack of mobile sediments and weak transport rates (Valerius et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations